Health Care Informatics Support of a Simulated Study - (:unkn) unknown (My University, 2012)
The objective of this project is to assess the value of REDCap (Harris, 2009) by conducting a simulated breast cancer clinical trial and demonstration. REDCap is a free, secure, web-based application designed to support data capture for research studies. To assess REDCap's value, we conducted a simulation of a clinical trial study designed to compare the use of two new technologies for breast cancer diagnosis and treatment with current best practice breast cancer diagnosis and treatment. We call the trial, "Real-Time Operating Room BC Diagnostic Treatment (RORBCDT)". The RORBCDT clinical trial is designed to assess the value of a new breast cancer operating room diagnostic technology "Intra-operative diagnosis of Sentinel Lymph Node (Sentimag)"( Keshtgar, n.d) and real-time treatment option "Intra-operative Radiotherapy (IORT)"( Williams, 2011.) A Sentimag is used to "stage" certain cancers to determine their degree of spread to lymph nodes. If the diagnose is positive, then the new treatment device (IORT) is used to treat the remaining cancerous tissue. This Clinical Trial simulation consists of several steps: 1. Design the clinical trial 2. Create the REDCap project environment to conduct the trial 3. Recruit and train fictitious patients, providers and project team. 4. Execute the simulated trial 5. Assess the value of REDCap in conducting the simulation. Note: This entire exercise is a SIMULATION - no actual patients, physicians or devices were used. Rather, a simulated clinical trial was performed with trained volunteers pretending to be patients, physicians and research staff. Consequently, the assessment of REDCap and all results, conclusions and observations are based on a SIMULATION. The simulated clinical trial - RORBCDT - is a two arm clinical trial designed to test the efficacy of the real-time diagnostic (Sentimag) and treatment (IORT) devices. In one arm of the trial, breast cancer surgery patients (volunteers not real patients) will experience a simulated best practice operation and therapy. In the other arm, breast cancer surgery patients (volunteers not real patients) will experience a simulated real-time diagnosis and treatment using the intra-operative devices. This research seeks to execute a fictitious clinical trial to assess the value of REDCap. We anticipate that this simulation and those similar to it, will help health care researchers become familiar with REDCap and assess REDCap's value and use in conducting health research.
Keywords: Clinical Trial; Data Capture; Health Care Informatics; Medical Informatics; Redcap